Implementation challenges in mass customisation: route bus design. (10th November 2010) - Napper, Robbie
The implementation of Mass Customisation (MC) in bus manufacture presents two difficulties in light of current MC theory – the application of MC in a bespoke industry and the creation of capital goods. Bespoke industries are characterised by customer involvement and customised goods; i.e., meeting the needs of customers but not efficient manufacture. MC for capital goods presents differences from needs elicitation methods, and changes the theory surrounding product value, customers and utility. These issues are explored through the specific challenges met in the bus bodywork industry. The research opens the discussion on bespoke manufacturing, finds that bespoke and capital goods industries can benefit from MC, and ultimately uses this contrast to contribute to existing MC theory.